Toward plasmonic monitoring of surface effects on bacterial quorum-sensing. (November 2017) - Hill, Eric H.; Liz-Marzán, Luis M.
Abstract: Biofilm formation is facilitated by cell–cell communication processes known as quorum sensing, which enable collective behavior and metabolic coordination. Surface topography and chemistry play a significant role in bacterial adhesion and biofilm formation, yet methods for monitoring quorum sensing in situ suffer limitations. Herein we suggest the use of surface-enhanced Raman scattering to study the effects of surface topography and chemistry on quorum sensing signals involved in biofilm growth. Graphical abstract: